Institutional Sustainability of Local Colleges and Universities (LCUs) in Region: an Evaluation - Gamboa, Alberto G. (Future Science / FSH-PH Publications, 2022)
The study aims to have a comprehensive assessment of the institutional sustainability of the Local Colleges and Universities (LCUs) in Region III. The focus of the evaluative study is on the areas of Governance and Management, Quality of Teaching and Learning, Quality of Professional Exposure, Research, and Creative Work, Support for Students, Relations with the Community, Teaching, and Student’s Involvement. 64 respondents for this study evaluated their institutions using the CHEd ISA Tool and the Unit based Sustainability Assessment Tool. Documentary materials and unstructured interview were also utilized to supplement the data gathered through the assessment tools. It was found out that the LCUs in Region III for the Academic Year 2013-2014 are very sustainable. The number of years of operations of the LCUs in Region III does not affect the institutional sustainability assessment in the key results area of Governance and Management, Quality of Teaching and Learning, Quality of Professional Exposure, Research, and Creative Work, Relations with the Community, (USAT) Curriculum, Teaching Approach, Research and Scholarship Activities, Community Engagement, Examination (Assessment) of Sustainability Topics, and Staff Expertise and Willingness to Participate. On the other hand, the number of years of operations of the LCUs in Region affects the institutional sustainability assessment in the key result area of Support for Students and Student’s Involvement. That is why the Administrators have plans and strategies that have thought to strengthen the institution’s commitment to sustainability.